1964
DOI: 10.1152/jappl.1964.19.1.142
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a brief contraction of forearm muscles on forearm blood flow

Abstract: With the use of a strain-gauge plethysmograph, the effect of a brief (0.3 sec) contraction of the forearm muscles on forearm blood flow has been studied in eight healthy adults. An increase in flow due to dilatation of the muscle vessels could be detected within a second after the completion of the contraction. This increase was proportional to the strength of the contraction. The blood flow was maximal immediately and decreased rapidly. A second contraction of the same magnitude made during the period of incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
115
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(128 citation statements)
references
References 0 publications
12
115
1
Order By: Relevance
“…Although there is an immediate increase in blood flow to active skeletal muscle with the onset of exercise (1,10,11,15,17,19,20), the mechanism(s) by which this rapid increase in blood flow occurs has remained elusive. The muscle pump theory has been proposed as a rapid, local mechanism by which blood flow to active skeletal muscle can be regulated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there is an immediate increase in blood flow to active skeletal muscle with the onset of exercise (1,10,11,15,17,19,20), the mechanism(s) by which this rapid increase in blood flow occurs has remained elusive. The muscle pump theory has been proposed as a rapid, local mechanism by which blood flow to active skeletal muscle can be regulated.…”
Section: Discussionmentioning
confidence: 99%
“…On relaxation, it is hypothesized that the muscle fibers that are tethered to the walls of the veins open the lumen of the compliant vessels and create low pressure (7, 9). Because the venous circulation contains one-way valves, oneway flow is ensured, and the enhanced arteriovenous pressure gradient results in an increase in arterial inflow to skeletal muscle (7).Studies employing both human and animal models have shown that skeletal muscle blood flow is significantly elevated within 1 s after the release of a brief tetanic contraction (1,15,19). Despite this rapid blood flow response in vivo, direct observations of arteriolar diameter reveal that dilation of the skeletal muscle arterioles occurs more slowly (4, 6, 21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 in Clifford and Hellsten (5)]. In fact, even a single muscle contraction produces a prompt increase in blood flow (1,7,14,26,36,39). There has been a debate over the last few decades about whether this rapid hyperemia is due to the muscle pump mechanism or to rapid vasodilation (5, 35).…”
mentioning
confidence: 99%
“…SKELETAL MUSCLE BLOOD FLOW has long been known to exhibit a rapid increase at the onset of exercise (1,9,12,22,27). The mechanisms behind this phenomenon are still a matter of debate despite the many new insights provided by different research groups in recent years.…”
mentioning
confidence: 99%